Prone positioning reduces frontal and hippocampal neuronal dysfunction in a murine model of ventilator-induced lung injury - Sparrow, Nicklaus A.; Guidry, Gena; Anwar, Faizan; Darwish, Sonja; Kelly, Scott A.; Karumanchi, S. Ananth; Lahiri, Shouri (Frontiers in Medicine, 2022)
Prone positioning is an established treatment for severe acute lung injury conditions. Neuronal dysfunction frequently occurs with mechanical ventilation-induced acute lung injury (VILI) and clinically manifests as delirium. We previously reported a pathological role for systemic interleukin 6 (IL-6) in mediating neuronal injury. However, currently no studies have investigated the relationship between prone or supine positioning and IL-6 mediated neuronal dysfunction. Here, we hypothesize that prone positioning mitigates neuronal injury, via decreased IL-6, in a model of VILI. VILI was induced by subjecting C57BL/6J mice to high tidal volume (35 cc/kg) mechanical ventilation. Neuronal injury markers [cleaved caspase-3 (CC3), c-fos, heat shock protein 90 (Hsp90)] and inflammatory cytokines (IL-6, IL-1β, TNF-α) were measured in the frontal cortex and hippocampus. We found statistically significantly less neuronal injury (CC3, c-Fos, Hsp90) and inflammatory cytokines (IL-6, IL-1β, TNF-α) in the frontal cortex and hippocampus with prone compared to supine positioning ( p < 0.001) despite no significant group differences in oxygen saturation or inflammatory infiltrates in the bronchoalveolar fluid (p > 0.05). Although there were no group differences in plasma IL-6 concentrations, there was significantly less cortical and hippocampal IL-6 in the prone position (p < 0.0001), indicating supine positioning may enhance brain susceptibility to systemic IL-6 during VILI via the IL-6 trans-signaling pathway. These findings call for future clinical studies to assess the relationship between prone positioning and delirium and for investigations into novel diagnostic or therapeutic paradigms to mitigate delirium by reducing expression of systemic and cerebral IL-6.